Institutional arrangements for the implementation of local economic development in Gauteng Province, with special reference to the City of Tshwane Metropolitan Municipality - Matlala, Ramolobi L.G. (My University, 2015)
Successful implementation of Local Economic Developed (LED) remains a key policy issue in Gauteng Province. The purpose of this exploratory study was to investigate the roles of the Gauteng Departments of Local Government and Housing (DLGH), and Economic Development (DED) in supporting the City of Tshwane Metropolitan Municipality (City of Tshwane) to implement LED initiatives successfully. The investigation adopted the single case study method, while data was collected by means of semi-structured interviews. The study confirmed that local economic development (LED) support is a multi-agency undertaking that involves national and provincial government agencies. The LED support process is nonetheless characterised by duplication of interventions, unsound IGR, unclear definition of roles, and poor coordination. The research study also found a disjuncture between the roles of the Gauteng Department of Economic Development and the Department of Local Government and Housing in LED support. The research study offers recommendations to improve the implementation of LED initiatives in the City of Tshwane.
Thesis (M.M. (Public Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Governance, 2014.